Religious and political leadership in Brazil at the turn of the 19th and 20th centuries – the case of Father Cícero - Siuda-Ambroziak, Renata Agnieszka (Revista Brasileira de História das Religiões, 2016)
Brazil is a very interesting place for academic research regarding religious and political leadership. It does not happen only due to the continuous supply of religious leaders, but also owing to their social and political influence. One of good examples of such leaders at the turn of the XIX and XX centuries is certainly Father Cicero, who, in spite of the problems connected with the disapproval of his activity on the part of the Vatican, is still regarded as a perfect example of both an outstanding politician and a non-canonized popular saint with the place of his earthly religious and political activity turned long ago into destination of pilgrimages and important popular religiosity shrines. Using the biographical method and coming out of the Weberian concepts of charismatic leadership, the author tries to explain the reasons behind his tremendous popularity and a conflict with the Catholic hierarchy, as well as to comment on the background of his cult in the context of social, economic and political changes taking place in Brazil during his lifetime.